Sex Differences in Social Attention in Infants at Risk for Autism - Kleberg, J.; Nyström, P.; Bölte, Sven; Falck-Ytter, T. (Springer New York LLC, 2018)
We studied visual attention to emotional faces in 10-month-old infant siblings of children with ASD (ASD-sibs; N = 70) and a siblings of typically developing children (N = 29) using static stimuli. Contrary to our predictions, we found no evidence for atypical gaze behavior in ASD-sibs when boys and girls were analyzed together. However, a sex difference was found in ASD-sibs' visual attention to the mouth. Male ASD-sibs looked more at the mouth across emotions compared to male controls and female ASD-sibs. In contrast, female ASD-sibs looked less at the mouth compared to female controls. These findings suggest that some aspects of early emerging atypical social attention in ASD-sibs may be sex specific.